Do government subsidies stimulate training expenditure? Microeconometric evidence from plant level data - Holger Görg; Eric Strobl (Institute for the Study of Labor (IZA), 2005)
This paper examines whether financial assistance provided by government induces firms to spend more of their own funds on training expenditures, using plant level data for the Republic of Ireland. We pay particular attention to the potential problems in such an evaluation study, namely selectivity and endogeneity, by first identifying a valid counterfactual for grant receiving plants via a matching estimator and then employing a difference-in-differences technique on this matched sample. Our results show that there are differences in causal effects between domestic and foreign owned plants. For the former we find clear evidence that grant receipt stimulates private expenditure, while there are no statistically significant effects for foreign-owned plants based in Ireland.
Keywords: 330; Subvention; Betriebliche Bildungsarbeit; Wirtschaftspolitische Wirkungsanalyse; Irland